2018
DOI: 10.1039/c8ra01206g
|View full text |Cite
|
Sign up to set email alerts
|

A novel adaptive ensemble classification framework for ADME prediction

Abstract: It has now become clear that in silico prediction of ADME (absorption, distribution, metabolism, and elimination) characteristics is an important component of the drug discovery process. Therefore, there has been considerable interest in the development of in silico modeling of ADME prediction in recent years. Despite the advances in this field, there remains challenges when facing the unbalanced and high dimensionality problems simultaneously. In this work, we introduce a novel adaptive ensemble classificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 80 publications
0
11
0
Order By: Relevance
“…To estimate their drug-likeness, the physicochemical characteristics of collected chemicals were compared with those of known drugs, according to their AMDE (absorption, metabolism, distribution, excretion). In 2012, Liang et al proposed that quantitative estimate of drug-likeness (QED) [ 28 , 29 ], an evaluation index of drug-likeness, could effectively estimate the AMDE of chemicals. QED was calculated using the following equation: …”
Section: Methodsmentioning
confidence: 99%
“…To estimate their drug-likeness, the physicochemical characteristics of collected chemicals were compared with those of known drugs, according to their AMDE (absorption, metabolism, distribution, excretion). In 2012, Liang et al proposed that quantitative estimate of drug-likeness (QED) [ 28 , 29 ], an evaluation index of drug-likeness, could effectively estimate the AMDE of chemicals. QED was calculated using the following equation: …”
Section: Methodsmentioning
confidence: 99%
“…Oral administration is the main route of administration for TCM. However, it is limited by the drug's ADME (absorption, distribution, metabolism, and elimination) characteristics [ 12 , 46 , 47 ]. The poor ADME properties are largely accountable for drug failure in exerting pharmacodynamic effect on target site in vivo [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…This measure of drug-likeness is calculated by integrating eight physicochemical properties of molecules [ 49 ]: (1) molecular mass, (2) number of hydrogen bond donors (HBDs), (3) octanol–water partition coefficient (ALOGP), (4) number of hydrogen bond acceptors (HBAs), (5) number of rotatable bonds (ROTBs), (6) number of aromatic rings (AROMs), (7) molecular polar surface area (PSA), and (8) number of structural alerts (ALERTS). Our previous work suggested that QED values can be used for the assessment of some ADME characteristics straightforwardly [ 46 ].…”
Section: Methodsmentioning
confidence: 99%
“…Ponzoni et al [116] used both engineered and learned molecular descriptors to construct a robust machine learning model with a collected dataset comprising 202 molecules. Wang et al and Yang et al [117,118] attempted to solve the data imbalance problem by a modified RF algorithm and various sampling methods, respectively. Both studies used molecular descriptors and conducted feature selection, but interestingly, Yang et al [118] designed the workflow to find optimal feature sets and the optimal ensemble model set.…”
Section: Absorptionmentioning
confidence: 99%
“…Specifically, most predictive models comprise hundreds to thousands of small chemistry datasets that cannot cover enough chemical space [76,118,188]. Moreover, the data is usually dispersed to many literatures [117,118,122,124,125,[128][129][130][134][135][136][137][138][139][140][141][142][143][144]150,155,[159][160][161][162][163][164][165][166][167][168][169]173,176,179,183], is unbalanced, and has cutoff ambiguity challenges [118,167]. Furthermore, the bioactivity assay data is strongly biased to its platform, and has an intrinsic experimental error which disrupts accurate prediction [189].…”
Section: Limitations and Future Directionmentioning
confidence: 99%